Canopy, Karfule - Ghosh, Ayan (2023)
Karfule is the only Art Deco petrol pump in Mumbai and one of two (Construction House is the other) buildings in Ballard Estate built in the late 1930s. The kiosk-like structure, with its octagonal canopy and star-shaped terrazzo tiles in the interior, was designed by GB Mhatre and Architectural Studio, one of the most prolific Art Deco architects of the era.